UPAYA PENINGKATAN KEMAMPUAN HAFALAN MUFRADAT BAHASA ARAB MELALUI METODE ASSAMSIYAH DI KELAS VII MTS BAHJATUL ULUM - Iqbal Al Faruq; Souheil Hallit (Learning, Media and Technology in Arabic Education, 2025)
This study aims to improve the memorization skills of Arabic mufradat (vocabulary) among seventh-grade students at MTs Bahjatul Ulum through the implementation of the Assamsiyah method. The main issue in Arabic language learning at the junior madrasah level often lies in the students’ weak mastery of vocabulary, which consequently affects other language skills such as reading (qirā’ah), writing (kitābah), speaking (kalām), and listening (istimā‘). The Assamsiyah method, developed through a musical and rhythmic approach, is believed to enhance students’ memory and retention of the mufradat being taught. This study employed a Classroom Action Research (CAR) approach conducted in two cycles over the course of one month, involving 20 seventh-grade students as research subjects. Data were collected through vocabulary memorization tests, observations, and interviews. The findings revealed a significant improvement in students’ memorization abilities from the first to the second cycle, both in terms of the number of vocabulary items remembered and their activeness during the learning process. Therefore, the application of the Assamsiyah method proved to be effective in enhancing students’ ability to memorize Arabic mufradat at the junior madrasah level